Double dissociation of error inhibition and correction deficits after basal ganglia or dorsomedial frontal damage in humans. (March 2015) - Hochman, Eldad Yitzhak; Wang, Seqian; Milner, Theodor E.; Fellows, Lesley K.
Abstract: Effective self-control relies on the rapid adjustment of inappropriate responses. Understanding the brain basis of these processes has the potential to inform neurobiological models of the many neuropsychiatric disorders that are marked by maladaptive responding. Research on error processing in particular has implicated the dorsomedial frontal lobe (DMF) and basal ganglia (BG) in error detection, inhibition and correction. However there is controversy regarding the specific contributions of these regions to each of these component processes. Here we examined the effects of lesions affecting DMF or BG on these error-related processes. A flanker task was used to induce errors that in turn led to spontaneous, online corrections, while response kinematics were measured with high spatiotemporal resolution. The acceleration of errors was initially greater than that of correct responses. Errors then showed slower acceleration compared to correct responses, consistent with engagement of inhibition shortly after error response onset. BG damage disproportionately disrupted this early inhibitory phenomenon, above and beyond effects on baseline motor performance, but did not affect the kinematics of the corrective response. DMF damage showed the opposite pattern, with relatively delayed onset and weaker initial acceleration of the corrective response, but error suppression kinematics similar to that of the control group. This work clarifies the component processes and neural substrates of online post-error control, providing evidence for dissociable contributions of BG to error inhibition, but not correction, and DMF to rapid error correction, but not error suppression. Highlights: The kinematics of flanker task errors suggest an active error inhibition process. Basal ganglia damage slows error inhibition without affecting correction kinematics. Dorsomedial frontal damage slows error correction, but spares error inhibition.